Role of judges of the Republic of Kazakhstan in the fight against the pandemic - Salpekov A.S.м (Bulletin of the Karaganda University “Law Series”, 2020)
The relevance of the research topic is evidenced by the fact that March 11, 2020 The world health organization has announced the COVID-19 pandemic. The Supreme court of the Republic of Kazakhstan for implementation of the Decree of the President of Kazakhstan K. Tokayev «On the introduction in the Republic of a national emergency» has a remote mode of operation. This article describes the features of conducting judicial proceedings by judges in online mode. The purpose of the study is to determine the role of a judge in the consideration of a case during specific conditions — a state of emergency. Methods that have been nvestigated. While working on the article, the author analyzed the current legislation. Methods of specific informational, logical and statistical analyses were used. The author’s experience as a judge, as well as real experience as a lawyer, was used to substantiate proposals for improving legislation. The result has been reached. The article attempts to define the legal status of a judge in a state of emergency, to reveal the dynamics and main directions of a judge when considering online trials. Brief conclusion: вased on the results of the research, the author has developed scientific recommendations for improving civil procedure legislation by analogy with criminal procedure legislation.